Social and economic barriers to adherence among patients at Livingstone General Hospital in Zambia - Kaala Moomba; Brian van Wyk (AOSIS, 2019)
Background: Zambia is one of the countries hardest hit by the human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) pandemic with a national HIV prevalence estimated at 14% among those aged 15-49 years in 2012. Antiretroviral therapy (ART) has been available in public health facilities in Zambia since 2003. By early 2016, 65% of the 1.2 million Zambians living with HIV were accessing ART. While access to ART has improved the lives of people living with HIV globally, the lack of adherence to ART is a major challenge to treatment success globally. Aim: This article reports on social and economic barriers to ART adherence among HIV patients being attended to at Livingstone General Hospital in Zambia. Setting: Livingstone General Hospital is located in the Southern province of Zambia, and had over 7000 patients enrolled for HIV care of whom 3880 patients were on ART. Methods: An explorative, qualitative study was conducted with 42 patients on ART where data were collected through six focus group discussions (3 male and 3 female groups) and seven in-depth interviews. Data were audio-recorded and transcribed verbatim and subjected to thematic content analysis. Results: Economic factors such as poverty and unemployment and the lack of food were reported as major barriers to adherence. Furthermore, social factors such as traditional medicine, religion, lack of family and partner support, and disclosure were also reported as critical barriers to adherence to ART. Conclusion: Interventions to improve adherence among ART patients should aim to redress the socio-economic challenges at community and individual levels.